"Ikwa i ja" - wiersz okolicznościowy, próba rozrachunku z romantyzmem czy utwór "domowy"? - Cieślak, Tomasz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
This essay is an attempt to analyze Ikwa i ja [The Ikva River and Me], a poem by Jarosław Iwaszkiewicz (1894–1980). It was first published on 26 June 1927 in “Wiadomości Literackie” and then in the volume Return to Europe (1931). The poem was written during the re-burial of Juliusz Słowacki (1809–1849), when the poet’s remains were relocated from Paris to Krakow. Iwaszkiewicz participated in these celebrations. In the absence of a direct echo of these events, Ikwa i ja is not only an occasional poem. It can also be regarded as an attempt to verify the importance of Słowacki’s achievements and perhaps more broadly — the importance of the romantic paradigm for the modern culture of the 1920s. The construction of the poem also shows its personal, intimate character for Iwaszkiewicz as he spent his childhood in the same place as Słowacki, namely in the Ukraine.